Correlation Between Mother’s Infants and Young Child Feeding (IYCF) Knowledge with Nutritional Status of Toddlers - Rani Rahmasari Tanuwijaya; Wahyu Permata Sri Tunggal Djati; Saskiyanto Manggabarani (Study Program of Nutrition, Public Health Faculty, Institut Kesehatan Helvetia, 2020)
Background: Nutrition is one of the essential parts of the child's growth and development phase. Adequate nutrition intake since the early stage is associated with the nutritional status of children. One factor that affects nutritional status improvement is an appropriate infant and young child feeding (IYCF). Another important factor of the successful IYCF is the mother's infant and young child feeding (IYCF) knowledge.Subjects and method: The design of this study was a descriptive-analytic study using a cross-sectional approach. This research was conducted in Pagelaran Village, Pagelaran District, Pandeglang. The study sample was 92 mothers of toddlers. The data were collected using a questionnaire about IYCF knowledge and were analyzed using the Chi-Square test.Result: This study showed that there was no significant correlation between mother’s IYCF knowledge and nutrition status of weight-for-age (p=0.088), length/height-for-age (p=0.226), and weight-for-height or weight-for-length (p=0.226).Conclusion: The mother's knowledge of IYCF has a vital role in the success of IYCF and will improve children's nutritional status.